The risk of ultraviolet exposure for melanoma in Fitzpatrick skin types I–IV: A 20‐year systematic review with meta‐analysis for sunburns - Kwa, Michael; Ravi, Manisha; Elhage, Kareem; Schultz, Lonni; Lim, Henry W. (Journal of the European Academy of Dermatology and Venereology, 2025)
Within the last two decades, no studies have comprehensively reviewed the risk of varying types of ultraviolet (UV) exposure on melanoma in fairer skinned individuals. Our research objective was to determine whether or not there was a change in the risk of UV exposure with development of melanoma in Fitzpatrick skin types I–IV based on more recent data over the past 20 years. We performed a systematic review from January 2002 to December 2021 analysing UV exposure and melanoma risk in Fitzpatrick type I–IV individuals. Out of 19,852 studies, 26 met inclusion criteria. Data spanned subjects from national and multinational cohorts (USA, Europe, Australia, Asia and South America). Twenty studies (77%, 20/26) identified a significant association between UV exposure and melanoma incidence. Sunburn was the most commonly assessed risk factor. Sunburn studies encompassed 3417 melanoma and found positive significant odds ratios (OR [95% CI]) in 11 out of 13 studies, ranging from 1.23 [1.01–1.49] to 8.48 [4.35–16.54]. Pooled analysis of the risk of melanoma with sunburn history found an unadjusted odds ratio of 1.66 [1.40–1.97] and adjusted odds ratio of 1.23 [1.04–1.46]. Cumulative sun exposure, measured as number of hours of sun exposure or calculated UV flux, was the second most common risk factor, encompassing 913 melanomas with positive significant ORs ranging from 1.1 [1.0–1.2] to 5.2 [2.1–12.5]. For other forms of UV exposure, a majority of studies showed an association with UV index (6/9), outdoor leisure activity (3/3) and left‐sided laterality (1/1). Overall, UV exposure should continue to be considered a modifiable risk factor for melanoma in individuals of fairer skin. Risk of ultraviolet exposure and melanoma in Fitzpatrick skin types I–IV. A systematic review of 19,852 studies from January 2002 to December 2021 was performed analysing UV exposure and melanoma risk in Fitzpatrick type I–IV individuals. Twenty studies (77%, 20/26) identified a significant association between UV exposure and melanoma incidence. There is a significant ongoing association between UV exposure, specifically sunburns (unadjusted odds ratio:1.66; pooled adjusted odds ratio: 1.23) and melanoma incidence in Fitzpatrick skin types I–IV. Other forms of UV exposure were more heterogeneously captured and had mixed results. UV exposure should continue to be considered a modifiable risk factor for melanoma in individuals of Fitzpatrick skin types I–IV. Counselling on photoprotection remains valuable for mitigating the risk of melanoma in this population. Thank you to Rebecca S. Xu, MD, for creating the images for use in this graphical .